Hydrogen Evolution: Self‐Limited on‐Site Conversion of MoO3 Nanodots into Vertically Aligned Ultrasmall Monolayer MoS2 for Efficient Hydrogen Evolution (Adv. Energy Mater. 21/2018). Issue 21 (25th July 2018) - Huang, Lin‐Bo; Zhao, Lu; Zhang, Yun; Chen, Yu‐Yun; Zhang, Qing‐Hua; Luo, Hao; Zhang, Xing; Tang, Tang; Gu, Lin; Hu, Jin‐Song
Abstract : In article number1800734, by Yun Zhang, Jin‐Song Hu and co‐workers, a self‐limited on‐site conversion strategy is developed to achieve well‐dispersed ultrasmall MoS2 monolayers. By vertically‐aligning and downsizing these monolayers to maximize the accessible highly‐active catalytic sites, they exhibit superior electrocatalytic performance for hydrogen evolution, suggesting that the present strategy opens up opportunities for exploring well‐dispersed ultrasmall nanomaterials as efficient catalysts.